The Impact of Barley α-Glucosidases on Mashing and the Production of Fermentable Sugars. (2nd October 2021) - Im, Hana; Henson, Cynthia A.
Abstract: The independent and interactive contributions of α-glucosidase to the degradation of raw starch isolated from barley and to the degradation of Lintner starch have been mathematically evaluated, but its contributions to the production of fermentable sugars during the actual mashing process have not been previously determined. Here we report the evaluation of those contributions through the use of an active site inhibitor, conduritol B epoxide, that specifically inhibits only α-glucosidase and has no effects on either α-amylase or β-amylase activities. Introduction of the inhibitor at the beginning of mashing resulted in the reduction of glucose produced by 20 − 30% throughout mashing and the reduction of maltotriose by 15 − 30%. Maltose levels were less influenced by α-glucosidase activities than were the levels of glucose and maltotriose. Hence, even though α-glucosidases are considerably thermolabile at temperatures often used for starch conversion, they can contribute significantly to the production of two of the three fermentable sugars generated from starch degradation during mashing. Additionally, we demonstrate that kilning resulted in a 12 − 34% loss of α-glucosidase activity, that 50-60% of the total activity was solubilized during mashing, most activity solubilized survived until mashing temperatures reached 55 °C, and that when mash temperatures reached 72 °C, α-glucosidase activity was rapidly inactivated.